Tin re-deposition and erosion measured by cavity-ring-down-spectroscopy under a high flux plasma beam. (14th July 2017) - Kvon, V.; Al, R.; Bystrov, K.; Peeters, F.J.J.; van de Sanden, M.C.M.; Morgan, T.W.
Abstract: Cavity-ring-down spectroscopy (CRDS) was implemented to measure the re-deposition of liquid tin under a high flux plasma beam in the linear plasma device Pilot-PSI. A capillary porous system (CPS) consisting of a molybdenum cup and tungsten meshes (pores diameters of 0.2 mm and 0.44 mm) was filled with tin and exposed to argon plasma. The absorption of a UV laser-beam at 286.331 nm was used to determine a number of sputtered neutral tin atoms. The incoming flux of argon ions of ~50 eV was 1.6–2.7  ×  10 23 m −2 s −1, and the sample temperature measured by pyrometry varied from 850 °C to 1200 °C during exposures. The use of CRDS for measuring absolute number of particles under such plasma exposure was demonstrated for the first time. The number of sputtered tin particles in the cavity region assuming no losses would be expected to be 5.5  ×  10 11 –1.2  ×  10 12 while CRDS measurements showed only 5.7–9.9  ×  10 8 . About 98–99.8% of sputtered particles were therefore found to not reach the CRDS observation volume. Spectroscopic ratios of Sn I to Sn II ions, as well as equilibrium considerations, indicate that fast ionization as well as plasma entrainment of neutrals is responsible for the discrepancy. This would lead to high re-deposition rates, implying a lowered contamination rate of core plasma and lower required replenishment rates at high-flux conditions than would otherwise be expected.